Spatial Analysis of the Assessment of Groundwater Validity for Drinking, Irrigation and animal Watering in Sinjar District Using GIS - Raed Mahmood Faysal (College of Education for Pure Sciences, 2013)
ABSTRACT: Groundwater occupies the forefront in areas where there are no sources of surface water from rivers and irrigation projects, and this applies to the study of sector Sinjar, located in the north-west of Iraq and of area (2926.4) km 2, as shown in the map (1), The water is a groundwater source upon which the main population of the judiciary for the purposes of drinking is primarily class, for the purposes of irrigation second class, has increased the role and importance of groundwater in the region with the increase in population, with repeated years of drought in the recent period, especially that the region relies mainly on rainwater in investment agriculture in the judiciary, therefore, stand on the validity of groundwater for human consumption and agricultural and through the application of modern techniques was using the (GIS), in analysis, and spatial distribution of the quality characteristics of groundwater in the study area is of significant importance.